Sedimentary architecture of sand bodies in the shallow marine Endalen Member, Firkanten Formation (Paleocene) of the Adventdalen Area, Svalbard - Grasdal, Øystein (The University of Bergen, 2018)
The Firkanten Formation has been the object of many research projects, but due to the economic interests in the lower coal bearing Todalen Member, the upper Endalen Member has received little attention. The Endalen Member is well marked in the mountain sides of the Adventdalen area, representing a succession of shallow marine shoreface sandstones. The close network of valleys cutting through the stratigraphy in this area provide a unique spatial overview of the architectural development of this unit. From logs, ten lithofacies have been recognized, organized into five facies associations representing deposition ranging from offshore to continental environments. Three types of key surfaces have been found, and an architectural hierarchy of the elements has been established based on their relative apparent extent. With the use of lateral extensive photo-mosaics of outcrops, accompanied by traditional field logs, the spatial development within the Adventdalen area has been investigated. Four distinct parasequences have been observed, showing a progradational trend and basinward thinning. The internal architecture of these parasequences indicate different coastal morphologies showing a transition from a slightly embayed deltaic coastline to a linear, wave dominated coastline. This study improves the understanding of the depositional history and morphological evolution of the Endalen Member in the Adventdalen area. Masteroppgave i geovitenskap MAMN-GEOV GEOV399